Frequency-agile antennas for wireless communications - Petosa, Aldo 1966- (Artech House antennas and propagation library, 2014)
Mobile data subscriptions are expected to more than double and mobile wireless traffic to increase by more than tenfold over the next few years. Proliferation of smart phones, tablets, and other portable devices are placing greater demands for services such as web browsing, global positioning, video streaming, and video telephony. Many of the proposed solutions to deal with these demands will have a significant impact on antenna designs. Antennas with frequency agility are considered a promising technology to help implement these new solutions. This book provides readers with a sense of the capabilities of frequency-agile antennas (FAAs), the widely diverse methods for achieving tunability, the current achievable performance, and the challenges still facing FAA designs. This resource explores the many aspects of FAAs, including an examination of the metrics used to evaluate their performance, a review of the most commonly used antenna elements, an in-depth look at the wide variety of mechanisms for achieving tunability, and a comprehensive survey of diverse examples of FAA designs. The focus is on FAAs for wireless mobile communications with applications including handsets, laptops, wireless machine-to-machine communications, as well as larger, fixed designs such as cellular base station antennas